1997
DOI: 10.1002/(sici)1096-9063(199712)51:4<419::aid-ps658>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Selection for imidacloprid resistance in silverleaf whiteflies from the Imperial Valley and development of a hydroponic bioassay for resistance monitoring

Abstract: : A Ðeld-collected population of the silverleaf whiteÑy, Bemisia argentifolii, was selected with the nicotinyl compound, imidacloprid, over 32 generations to determine if resistance would develop when maintained under continuous selection pressure in a greenhouse. Resistance was slow to increase at Ðrst with low to moderate levels of resistance (RR from 6-to 17-fold) in the Ðrst 15 generations of selection. Further selection steadily led to higher levels of resistance, with the greatest resistance ratio at 82-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 15 publications
2
54
1
1
Order By: Relevance
“…Resistance to imidacloprid has been reported in a range of species including western flower thrips, Colorado potato beetle, German cockroach, and house fly (39,40). In silverleaf whitefly and green peach aphid, high resistance was obtained by continuous selection in the greenhouse (41,42). Previous studies from this laboratory also have shown that the brown planthopper (N. lugens) developed high resistance to imidacloprid after continuous selection (19,20).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Resistance to imidacloprid has been reported in a range of species including western flower thrips, Colorado potato beetle, German cockroach, and house fly (39,40). In silverleaf whitefly and green peach aphid, high resistance was obtained by continuous selection in the greenhouse (41,42). Previous studies from this laboratory also have shown that the brown planthopper (N. lugens) developed high resistance to imidacloprid after continuous selection (19,20).…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies from this laboratory also have shown that the brown planthopper (N. lugens) developed high resistance to imidacloprid after continuous selection (19,20). In some species with high resistance to imidacloprid, piperonyl butoxide had very strong synergistic effects on imidacloprid, suggesting that P450 monooxygenases may play important roles in imidacloprid resistance (41,42). Our previous studies of resistance to imidacloprid in N. lugens (19) revealed significant cross-resistance only to the insecticides that target nAChRs, suggesting that target insensitivity might play an important role in imidacloprid resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Their structural similarity, coupled with a likely common target site, nicotinic acetylcholine receptors in the post-synaptic region of insect nerves (Bai et al 1991), also raises the spectre of cross-resistance a¡ecting the group as a whole (Elbert et al 1996;. The risk of resistance is therefore considerable, and reinforced by the speed with which resistance to imidacloprid has developed in B. tabaci under sustained exposure to this chemical in the laboratory (Prabhakar et al 1997) and in greenhouses in southern Europe (Cahill et al 1996b). Given the current scale of imidacloprid use, further resistance outbreaks seem inevitable and it is essential to exploit these for de¢ning conditions under which chloronicotinyls might be used sustainably.…”
Section: (B) Newer Insecticidesmentioning
confidence: 99%
“…Neonicotinoid resistance by metabolic detoxification of the insecticide, arising initially due to selection by DDT, has been found in D. melanogaster (Daborn et al, 2002). Long-term selection in Bemisia tabaci produced strains up to 82-fold resistant (Prabhaker et al, 1997). A mutation in two nAChR asubunits of Nilaparvata lugens reduced radiolabelled insecticide binding in assays with vertebrate b-subunits (Liu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%